Zastosowanie octanu triamcinolonu w celu wizualizacji ciała szklistego w przebiegu witrektomii pars plana - Mańkowska, Anna; Rejdak, Robert; Nowomiejska, Katarzyna; Zagórski, Zbigniew (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Purpose: To retrospectively evaluate the efficacy of triamcinolone acetonide (TA) injection during pars plana vitrectomy, to facilitate the visualization of the internal limiting membrane (ILM), residual vitreous cortex (RVC) and preretinal membranes. Material and methods: Pars plana vitrectomy was performed in 164 patients due to rhematogenous retinal detachment, vitreous hemorrhage, macular hole, lens luxation, endophthalmitis, intraocular foreign body, malignant glaucoma, preretinal membrane and proliferative diabetic retinopathy. After surgical separation of the posterior vitreous and removal of any visible epiretinal membrane, TA suspension was injected over the posterior pole into the vitreous cavity. Then, visualized RVC was removed and ILM peeling was performed. Results: Upon intravitreal injection of TA, vitreous and ILM could be visualized by numerous particles of TA dispersed as white specks. RVC and ILM were completely removed in all patients. No complications related to the use of TA were encountered, even after complex procedures such as, vitrectomy combined with scleral buckling or phakoemulsification surgery in a long term follow up. Conclusions: Intraoperative visualization of RVC and ILM with intravitreal TA was found to be a useful adjunct to pars plana vitrectomy. This technique may facilitate both removal of epiretinal membrane and separation of vitreous, especially in patients with undetached vitreous.